The Decision-Making Experiences of Early Married Couples during Pregnancy and Childbirth - Siti Fatimah; Andari wuri astuti; Wantonoro Wantonoro (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Marriage and adolescent pregnancy have an effect on decision-making ability and an increased risk of complications during pregnancy and childbirth. The incidence of teenage pregnancy in 2019 was approximately 16.93% and increased to 17.03% in 2020 in South Kalimantan. This study aims to determine the decision-making experiences of underage marriage during pregnancy and childbirth in 2023. Methods: This qualitative study used a generic exploratory methodology. This study’s sample was selected using homogeneous purposive sampling to include five pairs of adolescents in Banjarmasin City. The research analysis used thematic analysis and was analyzed using NVivo. There are four major themes that emerge from the research findings: prior knowledge, skills, and preparedness to become parents, decision making, obstacles, and expectations. Teenagers who marry at a young age and have children younger than one year old lack the knowledge, skills, and maturity to become parents and are therefore incapable of making decisions. Parents and spouses have a significant impact on decision-making. During pregnancy and childbirth, decision-making autonomy is influenced by a lack of parental knowledge, skills, and preparation. It is expected that training and education that involve family decision-makers will increase the knowledge, skills, and readiness of couples to become parents